1989
DOI: 10.1159/000153871
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and Reproductive Health in Iraq

Abstract: This study investigated the consanguinity rate of 233 families with severely disturbed reproductive health, and compared it to that of 227 families with normal (moderate) levels of reproductive wastage and to that of 155 families with no reproductive disturbance. The results showed that the inbreeding coefficients of the three groups of families were 0.0358, 0.0241 and 0.0208, respectively. Furthermore, the rate of congenital malformations was found to be highly correlated with the consanguinity rate of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…Compared with other Middle Eastern countries, which follow the same religion and have similar traditions as Saudi Arabia, the consanguinity rates in our study population are higher than in Bahrain [23], Egypt [24][25][26] and Lebanon [27,28] but similar to that reported from Oman [29] and Yemen [30] and significantly lower than the rates in Jordan [31][32][33], Kuwait [34], Iraq [11] and UAE [35]. An interesting finding of our study was that the prevalence of consanguinity in the married women was significantly higher than in their parents.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Compared with other Middle Eastern countries, which follow the same religion and have similar traditions as Saudi Arabia, the consanguinity rates in our study population are higher than in Bahrain [23], Egypt [24][25][26] and Lebanon [27,28] but similar to that reported from Oman [29] and Yemen [30] and significantly lower than the rates in Jordan [31][32][33], Kuwait [34], Iraq [11] and UAE [35]. An interesting finding of our study was that the prevalence of consanguinity in the married women was significantly higher than in their parents.…”
Section: Resultssupporting
confidence: 73%
“…One of the major harmful effects is a higher frequency of rare autosomal recessive disorders in the offspring of consanguineous mating [17,16]. In addition, increased rates of morbidity and mortality have been directly related to the degree of inbreeding [11,48]. Furthermore, congenital malformations and inborn errors of metabolism have also been shown to occur at a higher rate in the offspring of cousin marriages [45,47].…”
Section: Consanguinity Has Several Advantages and Several Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the rate of congenital malformations among the offspring of consanguineous marriages is approximately 2.5 times higher than that among the offspring of unrelated parents (table 1) [15, 19, 20, 21, 22, 23, 24]. The main cause appears to be the expression in the offspring of autosomal recessive disorders, although congenital malformations that are structural in nature and that have not been classified as typical autosomal recessive conditions have also been demonstrated [24].…”
Section: Effects Of Consanguinity On Congenital Malformationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Consanguinity has a significant influence on child mortality and morbidity independent of other causes of death and disease. '3'14 Previous studies of mainly nonconsanguineous parents have found that once stillbirth or infant death has appeared in a family, the risk of recurrence in subsequent siblings is higher than the population risk.…”
mentioning
confidence: 99%